Pengembangan Potensi Manusia Melalui Pendidikan Islam dalam Membentuk Generasi Berilmu dan Berakhlak: Human Potential Development Through Islamic Education in Forming a Knowledgeable and Moral Generation - Giral Ilham Bagus Pramudiansyah; Muhamad Febrian Febrian; Intan Noraziza Making; Kamelia Maimunah (Litera Academica Publishing, 2026)
Islamic education plays an important role in developing human potential comprehensively, including intellectual, spiritual, moral, and social aspects. In the modern era marked by technological advancement and globalization, various challenges have emerged, such as moral crises, declining ethics, and low spiritual awareness among the younger generation. These conditions highlight the importance of Islamic education as a means of shaping a knowledgeable and moral generation. This study aims to analyze the role of Islamic education in developing human potential to form a knowledgeable, well-characterized, and morally upright generation based on the perspectives of the Qur’an and Hadith. This research employed a qualitative method using a library research approach. Data were collected from books, scientific journals, articles, and other relevant literature sources, then analyzed using content analysis techniques. The findings reveal that Islamic education emphasizes the balance between intellectual development and moral cultivation through the concepts of ta’lim, tarbiyah, and ta’dib. Islamic education also contributes to the development of intellectual, spiritual, physical, social, and leadership potentials of learners. Furthermore, teachers’ exemplary behavior, habituation of Islamic values, and the integration of knowledge with Islamic principles are essential factors in shaping the character of the younger generation. In conclusion, Islamic education remains a relevant educational system in facing modern challenges because it is capable of producing generations who are intelligent, faithful, and possess noble character. This study is expected to contribute to the development of Islamic education studies, particularly in the fields of character building and intellectual development among the younger generation.